Psychosocial factors associated with gestational diabetes mellitus: Systematic review of scope - maury mena, sara concepcion; Marín-Escobar, Juan Carlos; Maury, Antolín; Marín-Benítez, Andrea Carolina (Horizonte Sanitario, 2022)
Objective: To carry out a systematic review of scope on the psychosocial factors associated with gestational diabetes mellitus (GDM) to improve preventive interventions, avoid its complications and improve the quality of life of pregnant women.Materials and methods: A systematic review was carried out based on the PRISMA methodology in PubMed/Medline and Cochrane databases on studies of psychosocial factors in pregnant women, older than 18 years, with a diagnosis of GDM, published in the period 2010 to 2020. , in peer-reviewed journals in any language. Data extraction was done using a standardized form.Results: The search yielded 1787 articles, of which 102 were selected according to inclusion criteria. The main themes were found: conflicts with cultural practices, social stigma, influence of ethnicity/race, low educational level, quality of sleep, physical limitations, problems with breastfeeding, concern for one's own health/baby, low perception of the risk of GDM and DM2 in the future, stress/anxiety/depression, limited knowledge about GDM, lack of partner/family/social support, low levels of self-care/self-efficacy in glycemic control, lack of support from health professionals and Difficulty with lifestyle changes.Conclusions: The identified psychosocial factors should be integrated into existing prevention and promotion programs or new interventions. Interventions should not terminate pregnancy if the risk of developing DM2 after delivery is taken into account. The needs of multi-ethnic populations and demographically and socioeconomically vulnerable groups need to be addressed. Psychosocial factors associated with GDM should also be included in the development of future Clinical Practice Guidelines.Keywords: Gestational diabetes mellitus; Risk factor's; Prevention; Health promotion; Revision.